An intelligent wind turbine with yaw mechanism using machine learning to reduce high-cost sensors quantity - Subrotho Bhandari Abhi; Plabon Kumar Saha; A. Z. M. Tahmidul Kabir; Al Mamun Mizan; Mohammad Minhazur Rahman; Afrina Talukder Mimi; Md. Mainul Ahsan; Arpita Hoque; Humyra Nusrat (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In this paper, with the assistance of some tools and a machine learning model, a smart wind turbine was formed that eliminates some expensive sensors and reduces sensor complexity. Squirrel cage induction generator (SCIG) and six rotor blades make up the proposed design, and depending on the wind's direction, the turbine itself can rotate the rotor hub to produce energy more effectively. Additionally, two stepper motors are coupled to the yaw mechanism with the aid of the rotor hub, and the entire controlling procedure will depend on the direction of the wind. The rotor hub must continuously revolve in the same direction as the wind to maximize wind energy utilization. Additionally, to correctly predict wind degrees, a machine learning model was deployed. Random forest regression was used to train and predict the wind direction. The model is deployed in Raspberry Pi, where the incoming sensor values are being stored. Using the generated data, machine learning model was trained and it can be concluded that the model can potentially replace some of the expensive sensors to reduce cost. The model can be used for similar weather conditions only based on machine learning model and fewer sensors.